Peritraumatic distress associated with domestic violence - R. Jbir; L. Aribi; N. Mseddi; I. Chaari; F. Charfeddine; S. Ellouze; J. Aloulou (European Psychiatry, 2023)
Introduction The violence against women massively committed by their spouses is a scourge that transcends countries, ethnicities, cultures, classes social and age groups. This violence is traumatic and represents a serious attack on the physical integrity and mental health of the women who are victims Objectives To study the prevalence and predictors of peritraumatic distress among women victims of domestic violence Methods We contacted 122 women who consulted at the psychiatric emergency of ‘Hedi Chaker hospital’,Sfax examined in the context of medical expertise on the period between May 2021 until January 2022 A questionnaire regarding the violence was asked to responders .It included demographic and violence exposure questions and a scale applied during violence ‘Peritraumatic distress inventory’ Results The average age of women assaulted in our study was 35.6 ± 9.94 years (min=18,max=64). 78.7% (n=96) of ladies were of urban origin. The majority of them(44,3%) had secondary level education. The half of the population (51.6%) had an average socio-economic level. (86.1%) had children. 98.7%were victim of verbal violence,94.7% of physical violence, 97.3% of psychological violence and 54.7 %of sexual violence. 72.1% of women (N=88) developed peritraumatic distress related to the assault with a risk of developing post-traumatic stress disorder. Women who were threatened by their spouses were more in distress than others (0,04). Physically abused women using a knife developed more peritraumatic distress (p=0,02). Conclusions Domestic violence is a global public health problem, that calls for urgent actions.Peritraumatic distress linked to violence may lead to psychotraumatic disordersthat are the source for traumatized victims of great suffering mental health and a possible vital risk (suicide, risky behavior). Disclosure of Interest None Declared